(3TQM GdCSHGHs - (3fajS Hf YhV Hf Mcje GdcQeGfj, HQgGf GdOjf , HYO (B841 (3g` s ((3eMeO QVG Hf CHj GdMSf GdWHGWHGFjs)
(3ChdgG (B:s
(3GdMeO ddg bO cfJ ef Cgd HjJ eTghQjf HgPg GdUfGYI hGHJdjJ aj YfahGf GdUHi hQjYGf GdTHGH HeRGhdI GdYdGL hEUdGM GdeRGL hde jbfY faSj HJYde QDhS GdeSGFd s
(3BNQgG (B:s
(3hdYdGLg QO GdYXe GdeSJQNj Edi OGNd eMdg eSJbQg GdPj RGd Yfg hJVejOg HGdCVeOI GdJj ajgG bhI eTOOI ddYVh eNdhWI HeG dg bhI eSNfI eLaaI ddQWhHGJ GJab GJeGe gPg GdfSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8/44s
(3cTa GdXfhf (B1/27s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs